Theoretical Investigations on Entropy Generation and Work Lost Analysis of 4MW Rice Husk Fired Thermal Power Plant - Umar Shafiq; Omar Qazi M.; Ahmad Mukhtar; M. Ahsan Badr Khan (NUST Journal of Engineering Sciences, 2019)
Global survival and human comfort in now a day strongly depend upon energy and environment. In this research generalized thermodynamic model equations were subjected to 4MW rice husk fired thermal power plant in Pakistan for theoretical investigations on work lost and entropy generation to check the plant thermal performance and irreversibility’s and concluded that the entropy generation and work lost is highest in Furnace/Boiler that is 3487.12352 KWK-1 and 1039.685 ×103 respectively. The work lost in Furnace/Boiler is about 32.4641% while the overall efficiency of the power plant is 59.8917%.